When Yawning Occurs in Elephants - Rossman, Zoë T.; Hart, Benjamin L.; Greco, Brian J.; Young, Debbie; Padfield, Clare; Weidner, Lisa; Gates, Jennifer; Hart, Lynette A. (Frontiers in Veterinary Science, 2017)
Yawning is a widely recognized behavior in mammalian species. One would expect that elephants yawn, although to our knowledge, no one has reported observations of yawning in any species of elephant. After confirming a behavioral pattern matching the criteria of yawning in 2 Asian elephants in a zoological setting, this study was pursued with 9 captive African elephants (Loxodonta africana) at a private reserve in the Western Cape, South Africa, the Knysna Elephant Park. Observations were made in June -September and in December. In the daytime, handlers managed 7 of the elephants for guided interactions with visitors. At night, all elephants were maintained in a large enclosure with 6 having limited outdoor access. With infrared illumination, the elephants were continuously recorded by video cameras. During the nights the elephants typically had 1 to 3 recumbent sleeping/resting bouts, each lasting 1-2 hours. Yawning was a regular occurrence upon arousal from a recumbency, especially in the final recumbency of the night. Yawning was significantly more frequent in some elephants. Yawning was rare during the daytime and during periods of standing around in the enclosure at night. In 6 occurrences of likely contagious yawning, one elephant yawned upon seeing another elephant yawning upon arousal from a final recumbency; we recorded the sex and age category of the participants. The generality of yawning in both African and Asian elephants (Elephus maximus) in other environments was documented in video recordings from 39 zoological facilities. In summary, the study provides evidence that yawning does occur in both African and Asian elephants, and in African elephants, yawning was particularly associated with arousal from nighttime recumbencies.